Dual optimization method of radiofrequency and quasistatic field simulations for reduction of eddy currents generated on 7T radiofrequency coil shielding - Zhao, Yujuan; Zhao, Tiejun; Raval, Shailesh B.; Krishnamurthy, Narayanan; Zheng, Hai; Harris, Chad T.; Handler, William B.; Chronik, Blaine A.; Ibrahim, Tamer S. (Magnetic resonance in medicine, 2015)
Purpose To optimize the design of radiofrequency (RF) shielding of transmit coils at 7T and reduce eddy currents generated on the RF shielding when imaging with rapid gradient waveforms. Methods One set of a four‐element, 2 × 2 Tic‐Tac‐Toe head coil structure was selected and constructed to study eddy currents on the RF coil shielding. The generated eddy currents were quantitatively studied in the time and frequency domains. The RF characteristics were studied using the finite difference time domain method. Five different kinds of RF shielding were tested on a 7T MRI scanner with phantoms and in vivo human subjects. Results The eddy current simulation method was verified by the measurement results. Eddy currents induced by solid/intact and simple‐structured slotted RF shielding significantly distorted the gradient fields. Echo‐planar images, B1+ maps, and S matrix measurements verified that the proposed slot pattern suppressed the eddy currents while maintaining the RF characteristics of the transmit coil. Conclusion The presented dual‐optimization method could be used to design RF shielding and reduce the gradient field‐induced eddy currents while maintaining the RF characteristics of the transmit coil. Magn Reson Med 74:1461–1469, 2015. © 2014 Wiley Periodicals, Inc.